Energy Consumption in Ukraine - Okaryachenko, A.P. (Економічний вісник Донбасу, 2013)
This article has highlighted the need for analysis of the total energy consumption in the domestic economy, studied the power consumption in the economy of Ukraine for the 2002 - 2011 years, shows the trend in the volume of TPES, the supply of natural gas and other energy sources in Ukraine in 2002 - 2011, analyzed the structure of primary energy supply by sources of supply of energy resources; was considered energy efficiency as the investment in reducing energy consumption to meet the growing energy demand. У статті було виявлено необхідність аналізу загального енергоспоживання в межах національної економіки; досліджено енергоспоживання в економіці України за 2002 - 2011 рр.; наведено динаміку обсягів ЗППЕ, постачання природного газу та інших джерел енергії в Україні у 2002 - 2011 рр.; проаналізовано структуру первинного постачання енергії за джерелами постачання ПЕР; було розглянуто енергетичну ефективність як капіталовкладення у скорочення енергоспоживання для задоволення зростаючого попиту на енергію. В статье было выявлена необходимость анализа общего энергопотребления в рамках национальной экономики; исследовано энергопотребление в экономике Украины за 2002 - 2011 гг; приведена динамика объемов ОППЭ, поставки природного газа и других источников энергии в Украине в 2002 - 2011 гг; проанализирована структура первичной поставки энергии по источникам поставок ТЭР; была рассмотрена энергетическая эффективность как капиталовложение в сокращение энергопотребления для удовлетворения растущего спроса на энергию.